The phenomenon of contemplation: etymological and philosophical analysis - Khudaynazarov Nuraddin Shavkatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
There is still no clear approach to the social philosophical and epistemological interpretations of thinking in the scientific literature. Therefore, if we look at it in accordance with the mind, knowledge, worldview, our thoughts on this subject become clear.